MEDIASI HARGA SAHAM ANTARA PROFITABILITAS, INVESTMENT OPPORTUNITY SET (IOS) DAN NILAI PERUSAHAAN - Alden R. Rajagukguk; Joan Yuliana Hutapea (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2020)
The purpose of this study is to investigate the influence of Profitability (Net Profit Margin) and Investment Opportunity Set (Price Earning Ratio) to the firm’s value in the oil and gas company listed at Bursa Efek Indonesia (BEI) by the period of 2014-2018. Using purposive sampling techniques, there are 7 companies that being selected that fulfill the criteria for the research sample. The result shows that: 1) Profitabilty has not significant influence to the Price Share, 2) IOS has not significant influence to the Price Share, 3) Profitability has not significant influence to the firm value, 4) IOS has not significant influence to the Firm Value, 5) Price Share has not significant influence to the Firm Value, 6) Price Share can’t mediate the influence of Profitability to the Firm Value, 7)Price Share can’t mediate the influence of IOS to the Firm Value.